Strategi Pelaku Usaha dalam Memasarkan Produk Halal di Kalimantan Timur - Hervina, Hervina; Maryah, Dewi; Sayuri, Sayuri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2020)
This research was inspired by a comparative study conducted by researchers at the International Institute for Halal Research and Training (INHART), which is one of the halal studies from the International Islamic University Malaysia. So far, especially people in Indonesia are only familiar with halal studies regarding food and beverage boundaries, including services, dynamics and innovation, halal products developed at this study institution are innovative and developing. This research aims to determine the strategies of business actors in marketing halal products in East Kalimantan, especially in the Sengatta East Kutai area. Based on the author's data findings and the results of the analysis carried out, it can be concluded that there are three strategies carried out by business actors in Sengatta, East Kutai, namely segmenting, targeting and positioning. The form of market segmentation carried out by business actors in marketing halal products can be seen that the segmentation in question has indeed been formed as if it is aimed at a particular community. The community in question is for example work friends, or a campus alma mater, school alumni, members of the Taklim Council, a group of prayer congregations at a mosque or Langgar, a professional community, a community that has the same hobby. Regarding targets, the form of market segmentation carried out by business actors in marketing halal products, it can be seen that the segmentation in question has indeed been formed as if it is aimed at a particular community. The community in question is for example work friends, or a campus alma mater, school alumni, members of the Taklim Council, a group of prayer congregations at a mosque or langgar, a professional community, a community that has the same hobby. Meanwhile, with regard to positioning, business actors are required to carry out promotions using social media considering that geographically Sengatta is located in a region that has inadequate infrastructure which hampers economic flows.